Citizen-centric privacy requirements engineering framework / Nor Asiakin Hasbullah - Hasbullah, Nor Asiakin (Institute of Graduate Studies, UiTM, 2018)
The transformation government (t-government) or Government 2.0 was initiated by the UK in 2006 to enhance and restructure the flaws in e-government with three characteristic themes of citizen-centric in (i) service delivery; (ii) shared services culture and (iii) professionalism. The aim of t-government is to transform public services for the benefit of citizens, businesses, taxpayers and frontline staff. The tgovernment requires a citizen centric perspective that takes into account of the citizens’ needs and concern contrary to the traditional approach where systems designers view the citizens’ needs from the perspective of the government and ignoring the citizens’ perspectives due to constraints of cost. One concern of citizen centricity revolves around the issue of trust in e-government in upholding citizen’s privacy. The effectiveness of t-government that uphold citizens’ rights to privacy is enshrined in the delivery process, and that citizens’ views and perceptions of privacy contribute to informing that process. Currently, the citizencentric perspective of privacy requirement is not well understood. To fill this gap, this research undertook a study with the objectives of (i) To investigate the availability and the content of privacy policy in e-government websites (ii) To investigate citizen’s privacy perception through their privacy concern and willingness to participate in public opinion platform (iii) To investigate citizen’s privacy requirement’s and need through their privacy preferences (iv) To propose citizencentric privacy requirements engineering framework by facilitating citizen engagement in fulfilling citizen privacy requirements. A multistakeholder perspective inquiry of citizens’ privacy concern though survey on citizens’ perception of personal and sensitive information among the common citizens and a focus group interview with a group of participatory citizens from the professionals was conducted. From the data analysis, two important results were obtained. The first is the citizen-centric preference set based on the information classification of personal and sensitive information and the second is the sensitivity scale of privacy related information. These two results are configured into a reference table and sensitivity classification tools respectively and integrated in a citizen-centric privacy requirements engineering framework which was verified by a group of experts. The framework can be applied to determine citizen centric privacy preference in the requirements of t-government engineering process and the tool could be use as classifying method to classify sensitive and personal information for system design.